Citraan pada Lirik Lagu Karya Nadin Amizah Edisi 2023 - Azannabilla, Dwi; Fauzan, Akhmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This research aims to describe the use of imagery in the 2023 edition of Nadin Amizah's song lyrics. The author used a qualitative descriptive research type by focusing the research object on the use of imagery using a stylistic approach. This research data is in the form of words, phrases and sentences related to the types of imagery in the 2023 edition of Nadin Amizah's song lyrics. The data collection technique uses reading and note-taking techniques. For data validity techniques, this research focuses on testing the credibility of the data using triangulation. The analytical method used is descriptive, while the data analysis technique used is data reduction by summarizing or summarizing the main important things to give a clearer and easier to understand picture, presenting data by presenting it in the form of explaining or describing and classifying the data according to The main problem is differentiation in explaining the types of imagery so that they are neatly arranged and easy to understand. Drawing conclusions or verification is done by comparing the suitability of the statements of the research object with the meaning contained in the results in the form of a summary description of the entire content of the research. The choice of expressive words and language was the impetus for researchers to research the 2023 edition of Nadin Amizah's song. With this research, song lovers understand the meaning of the lyrics conveyed because the song lyrics have complex meanings so that listeners do not understand the message conveyed. The results of the research show that there is use of imagery in the form of visual imagery, auditory imagery, olfactory imagery, tactile imagery and movement imagery.